Cognitive impairment is associated with increased central arterial stiffness in an animal model of chronic kidney disease. (20th December 2022) - Grigorova, Yulia N; Fox, Shanaya; Long, Jeffrey M; Santos, Carla Rocha Dos; McDevitt, Ross A; Zernetkina, Valentina; Haghkar, Mahdi; Wei, Wen; Morrell, Christopher H; Juhasz, Ondrej; Sodhi, Komal; Rapp, Peter R.; et al.
Abstract: Background: The prevalence of cognitive impairment (CI) and dementia in end‐stage chronic kidney disease (CKD) has been estimated at 30‐60%. Cardiovascular diseases (CVD) including increased central arterial stiffness (CAS) accompany CKD development and contribute to CI. Elevated pulse wave velocity (PWV) is associated with higher mortality in CVD and CKD independently of blood pressure (BP). Marinobufagenin (MBG) is a pro‐fibrotic factor, which increases in CKD and contributes to CAS. The aim of this study was to determine whether CKD potentiates CI development via CAS and cardiovascular remodeling in a rat model of CKD. Method: Four months old male Sprague‐Dawley rats were fed with 0.25% adenine (n=19; CKD group) diet to induce CKD or regular diet (n=16; CTRL group) for 8 weeks. Body weight (BW), BP, heart rate (HR), aortic PWV (aPWV), and behavioral tests were conducted at the end of the study. The level of anxiety was tested in an open field test (OFT). Morris water maze (MWM) was used to test spatial memory. Blood was collected for measurements of plasma sodium, potassium, blood urea nitrogen (BUN), hematocrit and MBG. The data were analyzed using two‐tailed unpaired t‐test and linear regression. Result: Animals in the CKD group had higher levels of plasma creatinine and BUN, which indicate the development of CKD, higher plasma sodium, potassium, and MBG, and higher aPWV, lower hemoglobin, hematocrit, BW, HR, enlarged hearts, aortae, and kidneys, vs. CTRL group (Table 1). BP was similar in both groups. .Rats in CKD group spent less time in the center of open field compared to their CTRL counterparts, indicating increased anxiety‐like behavior (Figure 1 A, B). Although there was no difference in performance in MWM between the groups, there was a positive correlation between aortic weight and ability to find a hidden platform in the CKD group (Figure 1C). Conclusion: We demonstrated that CKD development in young Sprague‐Dawley rats was accompanied by increased CAS, estimated as aPWV, which developed in blood pressure‐independent manner. Higher PWV was associated with a higher level of anxiety, and aortic tissue remodeling was associated with spatial memory in CKD model. Supported by NIH/NIA IRP